The Role of Endothelial Cells and TNF-Receptor Superfamily Members in Lymphoid Organogenesis and Function During Health and Inflammation - Jeucken, Kim C. M.; Koning, Jasper J.; Mebius, Reina E.; Tas, Sander W. (Frontiers in Immunology, 2019)
Lymph nodes (LNs) are crucial for the orchestration of immune responses. LN reactions depend on interactions between incoming and local immune cells, and stromal cells. To mediate these cellular interactions an organized vascular network within the LN is necessary. In general, the LN vasculature can be divided into two components: blood vessels, which include the specialized high endothelial venules that recruit lymphocytes from the bloodstream, and lymphatic vessels. Signaling via TNF-receptor (R) superfamily (SF) members has been implicated as crucial for the development and function of LNs and the LN vasculature. In recent years the role of cell-specific signaling of TNFRSF members in different endothelial cell (EC) subsets and their roles in development and maintenance of lymphoid organs has been elucidated. Here, we discuss recent insights into EC-specific TNFRSF member signaling and highlight its importance in different EC subsets in lymphoid organogenesis and maintenance during health, and during lymphocyte activation and tertiary lymphoid organ formation in disease.